2017
DOI: 10.1002/pd.5077
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy, work-up, and outcomes of pregnancies with clubfoot detected by prenatal sonography

Abstract: Prenatal ultrasound diagnosis of clubfoot is more accurate in singletons with bilateral findings. Bilateral findings do not increase the likelihood of additional anomalies. Karyotyping should be considered even with isolated clubfoot. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 18 publications
2
44
0
Order By: Relevance
“…Eleven studies (264 fetuses) explored the prevalence of chromosomal anomalies in fetuses with a prenatal diagnosis of apparently isolated talipes. Overall, abnormal karyotype was present in 3.6% (95% CI 1.7%‐6.2%) of fetuses with isolated clubfeet on ultrasound.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies (264 fetuses) explored the prevalence of chromosomal anomalies in fetuses with a prenatal diagnosis of apparently isolated talipes. Overall, abnormal karyotype was present in 3.6% (95% CI 1.7%‐6.2%) of fetuses with isolated clubfeet on ultrasound.…”
Section: Resultsmentioning
confidence: 99%
“…However, when analyzing the incidence of abnormal karyotype following either genotypic or phenotypic assessment after birth, the rate of chromosomal anomalies was 2.3% (95% CI 1.2%‐3.6%). More importantly, when only including studies published in the last decade, the incidence of abnormal karyotype was 1.5% (95% CI 0.5%‐3.0%, I 2 0%; 8 studies, 4/339 fetuses) . It was not possible to explore the presence of pathogenic copy number variants, as there was only 1 study in which 2 fetuses were tested for these anomalies using CMA …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For statistical analysis, we stratified perinatal outcomes by IUFD, TOP, or live birth, and found that younger maternal age was associated with more favorable outcomes; this might be related to the higher rate of more complex syndromes in older women (data not shown) [11]. According to the literature, the mean maternal age of women with a congenital malformation of the fetal limb ranged between 22.1 and 31.5 years [9,10,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…A glance at the currently available literature reveals that researchers have been focusing on the perinatal outcomes associated with clubfeet [11][12][13][14], followed by toe/finger malformations [15], amniotic band syndrome [16], and other various pathologies, including limb reduction defects, arthrogryposis, polydactyly, and abnormal hand position [17]. Some reports have focused on the prenatal diagnostic assessment rather than the obstetric outcomes in this selected patient cohort [18,19].…”
Section: Introductionmentioning
confidence: 99%